2014
DOI: 10.1016/j.ijid.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Mortality indicators in pneumococcal meningitis: therapeutic implications

Abstract: Ceftriaxone alone is not adequate in the management of pneumococcal meningitis due to penicillin-resistant pneumococci, which is a major concern worldwide. Although vancomycin showed a trend towards improving the prognosis of pneumococcal meningitis, significant correlation in statistical terms could not be established in this study. Thus, further studies are needed for the optimization of pneumococcal meningitis treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
32
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 48 publications
6
32
0
6
Order By: Relevance
“…On the other hand, the data in the literature related to the efficacy of treatment in HSV-2 meningitis are rather unclear (25,26).The host parameters directly affect the course of central nervous system (CNS) infections. In different types of CNS infections, increasing age and lower GCS scores have long been known to be associated with poor outcomes (27)(28)(29). Our HME data were also in accordance with those regarding other infectious CNS disorders and with the initial reports of adult HME series (10,18,19).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the data in the literature related to the efficacy of treatment in HSV-2 meningitis are rather unclear (25,26).The host parameters directly affect the course of central nervous system (CNS) infections. In different types of CNS infections, increasing age and lower GCS scores have long been known to be associated with poor outcomes (27)(28)(29). Our HME data were also in accordance with those regarding other infectious CNS disorders and with the initial reports of adult HME series (10,18,19).…”
Section: Discussionsupporting
confidence: 89%
“…Pnömokoklardaki antibiyotik direnci incelendiğinde birçok ülkede 1980'li yıllardan sonra penisilin dirençli suşların her geçen gün artış gösterdiği saptanmaktadır (16)(17)(18)(19). S. pneumoniae'de bazı ülkelerde kontrollü antibiyotik kullanımı başta olmak üzere bazı önlemler alınarak direncin artışı kontrol altına alınmış, direnç düşüş gösterdiği gözlenmiştir (20)(21)(22) (23).…”
Section: Discussionunclassified
“…ID-IRI has produced bulk of information on pneumococcal meningitis [4], brucellar meningitis [5], tuberculous meningitis [6,7], and herpetic meningoencephalitis [8]. Among these CNS infection studies [5][6][7][8] are the largest case series ever reported in the literature.…”
Section: Brief Reportmentioning
confidence: 99%